INTEGRATING LOCAL PRODUCTS AND EXPERIENTIAL OFFERINGS TO ENHANCE THE COMPETITIVENESS OF PAKINTELAN TOURISM VILLAGE, SEMARANG - Aurilia Triani Aryaningtyas; Suwarti; Syamsul Hadi; Taletha Akila; Aura Astaningrum (STABN Raden Wijaya Wonogiri, 2026)
This study examines how the integration of local products and tourism experiences can enhance the competitiveness of Pakintelan Tourism Village in Semarang. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and document analysis involving key stakeholders. The findings show that local products function as cultural-symbolic resources but are still positioned as complementary elements rather than as core components of tourism experiences. Tourism activities remain fragmented, observation-based, and limited in fostering interaction, resulting in weak co-creation of experience and low visitor engagement. This study argues that competitiveness is not solely determined by resource availability, but by how these resources are transformed into meaningful experiences. It proposes a shift from a product-oriented approach to an experience-based approach, where local products serve as experiential media that enable participation and interaction. The study contributes by offering a meaning-based perspective on destination competitiveness within community-based tourism.